Effect of cecal microbiota transplantation on peripheral 5-hydroxytryptamine and breast muscle glucose metabolism in long-photoperiod broilers - Miao Yu; Mengjie Xu; Guangju Wang; Jinghai Feng; Minhong Zhang (Poultry Science, 2025)
Prolonged light periods resulted in up-regulation of cecal 5-hydroxytryptamine (5-HT) synthesis and secretion, disorders of breast muscle glucose metabolism and alteration in gut microbiota composition. The present study was conducted to investigate the effects of cecal microbiota on peripheral 5-HT metabolism and breast muscle glucose metabolism in broiler chickens underlying prolonged light periods. A total of 144 5-day-old male Arbor Acres (AA) broiler chickens were randomly divided into four treatment groups i.e., 12 hours light: 12 hours dark (12L:12D) photoperiod group, 18 hours light: 6 hours dark (18L:6D) photoperiod group, 18L:6D photoperiod with phosphate buffered saline (PBS) solution administration group (18L:6D+PBS) and 18L:6D photoperiod with cecal microbiota transplantation (CMT) group (18L:6D+CMT) for 14 days. The results demonstrated that the 18L:6D photoperiod increased breast muscle rate (P < 0.05) but induced the morphological damage of breast muscle, dysregulation of breast muscle glucose metabolism and higher peripheral 5-HT synthesis (P < 0.05). In contrast, CMT significantly improved breast muscle weight and breast muscle ratio while reducing the breast muscle injury. Furthermore, CMT alleviated glucose metabolism dysregulation, as evidenced by significant reductions in serum glucose (P < 0.05), insulin (INS) (P < 0.05), homeostasis model assessment of insulin resistance (HOMA-IR) (P < 0.05), and the lactic acid-to-pyruvate ratio (L/P) (P < 0.05), as well as an increase in muscle glycogen concentrations (P < 0.05). Additionally, the expression of glycogen synthase (GS), pyruvate dehydrogenase (PDH) and glucose transporter-4 (GLUT4) up-regulated, while the expression of glycogen phosphorylase L (PYGL), hexokinase (HK), 6-phosphofructokinase (PFK), pyruvate kinase (PK) and lactate dehydrogenase (LDH) down-regulated (P < 0.05) in breast muscle of CMT-treated broiler chickens. Notably, both peripheral 5-HT concentrations and cecal 5-HT synthesis was significantly reduced (P < 0.05) in the 18L:6D+CMT group. In summary, these findings indicate that CMT promotes breast muscle rate, reduces breast muscle injury, alleviates breast muscle glucose metabolism disorder in broiler chickens exposed to prolonged light periods. Moreover, peripheral 5-HT metabolism may serve as a key pathway through which cecal microbiota regulates skeletal muscle glucose metabolism.